1958
DOI: 10.1111/j.1467-6494.1958.tb01571.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of impulsivity, introversion, and individual values upon association under free conditions1

Abstract: The standard word-association test has, in general, been disappointing as a diagnostic tool Despite its sensitivity to S3miptoms of emotional maladjustment, it has failed to provide measures of other important aspects of the personahty Since modern clinical and experimental evidence indicates that temperament, attitudes, and values do influence associative processes, it seems plausible to suspect that the special conditions imposed in the standard test are responsible for Its failure to reflect these basic asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1964
1964
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…It has been found that associations are influenced by such things as past experience (Foley & l/lacIvIillan,19~·3), internal states (WisP~, 1954), and personality factors (Dunn, Bliss, & Siipola, 1958). This study has shown , in addi.t.Lon , that associations are influenced by the order of test items: certain sequences of items may induce a t.endency in 5s to avoid variation in the relationship between the response word and the stimulus word.…”
Section: About Herementioning
confidence: 50%
“…It has been found that associations are influenced by such things as past experience (Foley & l/lacIvIillan,19~·3), internal states (WisP~, 1954), and personality factors (Dunn, Bliss, & Siipola, 1958). This study has shown , in addi.t.Lon , that associations are influenced by the order of test items: certain sequences of items may induce a t.endency in 5s to avoid variation in the relationship between the response word and the stimulus word.…”
Section: About Herementioning
confidence: 50%
“…Viewing the experimental hypotheses in light of the results (see Table 1), the cultural-literary interest dimension, advanced by Jenkins (1960), and the inhibitionimpulsivity reference variable, advanced by Dunn et al (1958), are both important in the development of verbal behavior.…”
Section: Discussionmentioning
confidence: 96%
“…Carroll, Kje1dergaard, and Carton (1962) It has already been found that free-association responses are influenced by such things as past experience (Foley & MacMillan, 1943), internal states (wisp6, 1954, personality (Dunn, Bliss, & Siipola, 1958), self-instructions (Moran et al, 1964), and order of stimulus words (Wynne et al, 1965). given popular responses in a previous session, it seems likely that giving such responses again would simplify the~IS task since these responses should have relatively high associative strength.…”
Section: Discussionmentioning
confidence: 99%